Understanding the inhibitory effect of highly potent and selective archazolides binding to the vacuolar ATPase - Dreisigacker, Sandra; Menche, Dirk (Journal of chemical information and modeling, 2012)
Vacuolar ATPases are a potential therapeutic target because of their involvement in a variety of severe diseases such as osteoporosis or cancer. Archazolide A (1) and related analogs have been previously identiﬁed as selective inhibitors of V-ATPases with potency down to the subnanomolar range. Herein we report on the determination of the ligand binding mode by a combination of molecular docking, molecular dynamics simulations, and biochemical experiments, resulting in a sound model for the inhibitory mechanism of this class of putative anticancer agents. The binding site of archazolides was conﬁrmed to be located in the equatorial region of the membrane-embedded VO-rotor, as recently proposed on the basis of site-directed mutagenesis. Quantiﬁcation of the bioactivity of a series of archazolide derivatives, together with the docking-derived binding mode of archazolides to the V-ATPase, revealed favorable ligand proﬁles, which can guide the development of a simpliﬁed archazolide analog with potential therapeutic relevance.